2011
DOI: 10.1152/ajpheart.00516.2010
|View full text |Cite
|
Sign up to set email alerts
|

Early experimental hypertension preserves the myocardial microvasculature but aggravates cardiac injury distal to chronic coronary artery obstruction

Abstract: Coronary artery disease is a leading cause of death. Hypertension (HT) increases the incidence of cardiac events, but its effect on cardiac adaptation to coexisting coronary artery stenosis (CAS) is unclear. We hypothesized that concurrent HT modulates microvascular function in chronic CAS and aggravates microvascular remodeling and myocardial injury. Four groups of pigs ( n = 6 each) were studied: normal, CAS, HT, and CAS+HT. CAS and HT were induced by placing local irritant coils in the left circumflex coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…52 These findings support the concepts that endothelial dysfunction contributes to microvascular dysfunction distal to a stenosis, and does so via alterations in the control of vascular tone as well as through structural changes in microvessel diameter 5 and densities. 51 These findings indicate that a chronic epicardial stenosis may not only limit flow reserve by increasing proximal artery resistance, but also by producing microvascular dysfunction. This explains, at least in part, the observation that many patients with a significant coronary artery stenosis show an exaggerated reduction in coronary flow reserve for the level of stenosis severity.…”
Section: Regulation Of Cbf In Pathophysiological Statesmentioning
confidence: 88%
See 1 more Smart Citation
“…52 These findings support the concepts that endothelial dysfunction contributes to microvascular dysfunction distal to a stenosis, and does so via alterations in the control of vascular tone as well as through structural changes in microvessel diameter 5 and densities. 51 These findings indicate that a chronic epicardial stenosis may not only limit flow reserve by increasing proximal artery resistance, but also by producing microvascular dysfunction. This explains, at least in part, the observation that many patients with a significant coronary artery stenosis show an exaggerated reduction in coronary flow reserve for the level of stenosis severity.…”
Section: Regulation Of Cbf In Pathophysiological Statesmentioning
confidence: 88%
“…In contrast, there is evidence that a chronic coronary artery stenosis, not only results in myocardial and interstitial, 6,50 but also in structural and functional microvascular alterations distal to the stenotic artery. Thus, arteriolar inward remodeling 5 and rarefaction 51 have been reported, as well as increased vasoconstrictor responses to endothelin (due to a loss of ET B -mediated vasodilation) and blunting of myogenic responses. 52 These findings support the concepts that endothelial dysfunction contributes to microvascular dysfunction distal to a stenosis, and does so via alterations in the control of vascular tone as well as through structural changes in microvessel diameter 5 and densities.…”
Section: Regulation Of Cbf In Pathophysiological Statesmentioning
confidence: 99%
“…21 MDCT studies performed 2 days after MRI evaluated cardiac structure and function, as shown previously. 22 LV muscle mass, systolic function, early (E) and late (A) LV filling rates were calculated, as well as myocardial perfusion and MV permeability index before and during adenosine infusion, as we described. 20, 22, 23 Intra-abdominal adipose tissue measured using MDCT was expressed as volume and fraction.…”
Section: Methodsmentioning
confidence: 99%
“…22, 24, 25 Microvessels were classified using Analyze™ as small (diameters 20–200 µm), medium (201–300 µm), or large (301–500 µm). See Supplemental data for detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation